PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK TWO STAY TWO STRAY (TSTS ) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIIH SMPN 23 PEKANBARU - Noviana Noviana; Jalinus Jalinus; Syarifah Nur Siregar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRAKThis research was conducted in SMP 23 pekanbaru , in the first half of the school year 2012/2013 . Subjects were students of class VIII H totaling 40 people , comprising 20 boys and 20 girls who have the academic ability heterogeneous . The purpose of this research is to improve the students achievement., By implementing cooperative learning techniques TSTS . This research is a class act consisting of two cycles , each cycle consisting of four stages: planning , action , observation , and reflection . The data collected in this study is the activity data of teachers and learners during the learning and mathematics achievement data . Data activity of teachers and learners obtained from teacher observation sheets and sheets of observations of learners , while achievement data obtained from the test results of learners , the data were analyzed descriptively . The results of the data analysis and teacher activity suggests that the activity of teachers and learners increasingly according to the lesson plan , it is marked by the teacher to reflect on the learning process that has been done so that the improvement of the deficiencies that have been found . Analysis of students achievment increases , it can be seen from KKM achievement of learners achieved , in the first cycle of students who achieve KKM is 45 % and the silus II increased to 77.5 % of this data concluded that an increase due to the students achievement, KKM before action is only 27.5 % . Based on these results , the use of cooperative learning techniques TSTS can improve students achievement in class VIII H SMP N 23 Pekanbaru.Keywords: Cooperative Learning, Two Stay Two Stray (TSTS),students achievement